2016
DOI: 10.1097/aog.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Biweekly Research Workgroup With Enhanced Resident Research Productivity

Abstract: Almost all residency programs require a resident research project, yet teaching and mentoring of the required skills are often lacking. We established an every-other-week gynecologic oncology research workgroup at our institution for obstetrics and gynecology faculty, fellows, and residents with the goal of increasing resident research education, involvement, and productivity. An informal, discussion-style format was adopted as a forum for brainstorming research ideas, formulating study protocols, and collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The remaining locations, Germany [32] and India [26] had 1 (3%) article each. The disciplines studied were internal medicine (7, 22%), [18, 25, 27, 28, 32, 41, 42] orthopedic surgery (6, 19%), [29, 30, 33, 34, 38, 46] general surgery (5, 16%) [2123, 31, 36], pediatrics (3, 9%) [3, 7, 40], family medicine (3, 9%) [17, 24, 45], neurology (2, 6%) [26, 39] and obstetrics and gynecology (2, 6%), [19, 37] with otolaryngology [20], gastroenterology [35], anesthesiology [43], and pulmonary critical care [44] each in one article. Nineteen (19/32, 59%) studies reported sample sizes (number of participants) [3, 7, 17, 21, 22, 25, 27, 28, 30, 3236, 3840, 43, 46] ranging from 25 [17] to 527 [7], with 10/19 (53%) having sample sizes less than 100 [17, 21, 25, 27, 32, 34, 35, 38, 40, 46].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining locations, Germany [32] and India [26] had 1 (3%) article each. The disciplines studied were internal medicine (7, 22%), [18, 25, 27, 28, 32, 41, 42] orthopedic surgery (6, 19%), [29, 30, 33, 34, 38, 46] general surgery (5, 16%) [2123, 31, 36], pediatrics (3, 9%) [3, 7, 40], family medicine (3, 9%) [17, 24, 45], neurology (2, 6%) [26, 39] and obstetrics and gynecology (2, 6%), [19, 37] with otolaryngology [20], gastroenterology [35], anesthesiology [43], and pulmonary critical care [44] each in one article. Nineteen (19/32, 59%) studies reported sample sizes (number of participants) [3, 7, 17, 21, 22, 25, 27, 28, 30, 3236, 3840, 43, 46] ranging from 25 [17] to 527 [7], with 10/19 (53%) having sample sizes less than 100 [17, 21, 25, 27, 32, 34, 35, 38, 40, 46].…”
Section: Resultsmentioning
confidence: 99%
“…In addition they implemented monthly research forums and mentor meetings to discuss research related issues. Particular emphasis was given to projects that could be completed within a 1-month period and result in publication.Yes (Research elective: 1 month in PGY1 and PGY3 or up to 2 months in PGY2)Yes (faculty)Increase in scholarly activity from 2010 to 2011 to 2011–2012 by 110%.• 6 submissions with 2 abstracts accepted for presentation at the Louisiana Chapter of the American College of Physicians Associates meeting (2010–2011) compared to 14 submissions, with 4 accepted for presentation (2011–2012)• 4 submissions to the Southern Hospitalist Conference (2010–2011), which increased to 7 (2011–2012), with one receiving second place in the competitionN/A10Brackmann, et al, 2016 [19]Michigan, USAPre-post study using historical data as a comparison groupComparison group (27 months before) vs. (27 months after) workgroup discussionsBiweekly, voluntary (1–2 h) gynecologic oncology research workgroup. An informal, discussion-style format for brainstorming research ideas, formulating study protocols, and collaborating on institutional review board submissions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, collaborative trainee research programs with biweekly group research meetings have resulted in increased resident research productivity. 4 A supportive mentored research environment for trainees and early faculty should not be limited to interactions with other faculty/staff within cardiothoracic surgery. Research training, especially techniques to succeed in today's highpressure research environment, are unfortunately not part of standard curricula in medical school or residency.…”
Section: Early Mentored Research Environment Is Criticalmentioning
confidence: 99%